Q. 5 A3.9( 23 Votes )

Prove the followi

Answer :

Taking LHS


secθ(1 - sinθ) (secθ + tanθ)




[(a + b)(a - b) = a2 - b2]


[ sin2θ + cos2θ = 1]


= 1


= RHS


Proved !


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USMaharashtra Board - Geometry Papers

<span lang="EN-USMaharashtra Board - Geometry Papers

Prove that:
</
MHB - Mathematics Part-2

If <span lang="ENMHB - Mathematics Part-2

<span lang="EN-USMaharashtra Board - Geometry Papers

<span lang="EN-USMaharashtra Board - Geometry Papers

Prove the followiMHB - Mathematics Part-2

If tan θ = 2, finMHB - Mathematics Part-2

Prove that:
</
MHB - Mathematics Part-2

If <span lang="ENMHB - Mathematics Part-2